Nitrogen application timing and soil inorganic nitrogen dynamics under no-till oat/maize sequential cropping - Dieckow,Jeferson (2006)
The timing of N application to maize is a key factor to be considered in no-till oat/maize sequential cropping. This study aimed to evaluate the influence of pre-planting, planting and sidedress N application on oat residue decomposition, on soil N immobilisation and remineralisation and on N uptake by maize plants in no-till oat/maize sequential cropping. Undisturbed soil cores of 10 and 20 cm diameter were collected from the 0-15 cm layer of a no-till Red Latossol, when the oat cover crop was in the milk-grain stage. Two greenhouse experiments were conducted simultaneously. Experiment A, established in the 10 cm diameter cores and without plant cultivation, was used to asses N dynamics in soil and oat residues. Experiment B, established in the 20 cm diameter cores and with maize cultivation, was used to assess plant growth and N uptake. An amount of 6.0 Mg ha-1 dry matter of oat residues was spread on the surface of the cores. A rate of 90 kg N ha-1 applied as ammonium sulphate in both experiments was split in pre-planting, planting and sidedress applications as follows: (a) 00-00-00 (control), (b) 90-00-00 (pre-planting application, 20 days before planting), (c) 00-90-00 (planting application), (d) 00-30-60 (split in a planting and a sidedress application 31 days after emergence), (e) 00-00-00* (control, without oat residue) and (f) 90-00-00* (pre-planting application, without oat residue). The N concentration and N content in oat residues were not affected during decomposition by N fertilisation. Most of the fertiliser NH4+-N was converted into NO3--N within 20 days after application. A significant decrease in NO3--N contents in the 0-4 cm layer was observed in all treatments between 40 and 60 days after the oat residue placement on the soil surface, suggesting the occurrence of N immobilisation in this period. Considering that most of the inorganic N was converted into NO3- and that no immobilisation of the pre planting fertiliser N occurred at the time of its application, it was possible to conclude that pre-planting applied N was prone to losses by leaching. On the other hand, with split N applications, maize plants showed N deficiency symptoms before sidedress application. Two indications for fertiliser-N management in no-till oat/maize sequential cropping could be suggested: (a) in case of split application, the sidedress should be earlier than 30 days after emergence, and (b) if integral application is preferred to save field operations, this should be done at planting.